Optimization of Thermal System Performance to Improve Energy Efficiency - Yosua Luis Vigo; Agung Pratama; Sumarhadi sipahutar; Moh abdul munif (METALOGRAM, 2026)
This paper investigates the optimization of thermal system performance to improve energy efficiency using a quantitative simulation-based approach. Thermal systems are widely applied in industrial and building sectors, where inefficient heat transfer often results in excessive energy consumption. This study aims to evaluate key thermal performance parameters and analyze optimization strategies based on energy balance and heat transfer principles. Parametric simulations were conducted by varying insulation quality, operating temperature, and heat loss rates. The results show